Neuropathic Pain in Animal Models of Nervous System Autoimmune Diseases - David H. Tian; Chamini J. Perera; Gila Moalem-Taylor (Mediators of Inflammation)
Neuropathic pain is a frequent chronic presentation in autoimmune diseases of the nervous system, such as multiple sclerosis (MS) and Guillain-Barre syndrome (GBS), causing significant individual disablement and suffering. Animal models of experimental autoimmune encephalomyelitis (EAE) and experimental autoimmune neuritis (EAN) mimic many aspects of MS and GBS, respectively, and are well suited to study the pathophysiology of these autoimmune diseases. However, while much attention has been devoted to curative options, research into neuropathic pain mechanisms and relief has been somewhat lacking. Recent studies have demonstrated a variety of sensory abnormalities in different EAE and EAN models, which enable investigations of behavioural changes, underlying mechanisms, and potential pharmacotherapies for neuropathic pain associated with these diseases. This review examines the symptoms, mechanisms, and clinical therapeutic options in these conditions and highlights the value of EAE and EAN animal models for the study of neuropathic pain in MS and GBS.